Article Review : Acid Stress in Soybean (Glycine max L.) - Daniati, Nia; Violita (Microbiotech, 2024)
This study aims to identify soybean varieties that are adaptive to acid stress and evaluate the effect of acid stress on soybean growth and yield based on parameters such as plant height, number of nodes, dry weight, number of pods, seed weight, and root weight. The method used is a literature review using Google Scholar and Google Books databases. The results showed that acid stress significantly affected several growth parameters, such as plant height and dry seed weight, with the highest results on soil with a pH of 6. However, acid stress did not significantly affect the number of branches and root weight. Additionally, the inoculation of Rhizobium sp. and phosphate-solubilizing bacteria did not significantly increase soybean production in saline soil. The conclusion of this study suggests that developing soybean varieties tolerant to acid stress is crucial for improving soybean productivity in acidic soil conditions.